Partner involvement in abortion trajectories and subsequent abortion safety in Nigeria and Côte d'Ivoire - Selena Anjur-Dietrich; Elizabeth Omoluabi; Funmilola M. OlaOlorun; Rosine Mosso; Shannon N. Wood; Caroline Moreau; Suzanne O. Bell (BMC, 2022)
Abstract Background Unsafe abortions contribute to maternal mortality and morbidity worldwide, with disproportionate impacts in lower-income countries. Identifying factors associated with an elevated risk of experiencing an abortion under the most unsafe conditions is an important component of addressing this burden. The partner's role in obtaining a safe or unsafe abortion is not well understood. This study provides a quantitative assessment of the relationship between partner involvement and subsequent abortion safety. Methods The data are drawn from the PMA2020 female surveys and abortion follow-up surveys, fielded in Nigeria and Côte d'Ivoire between 2018 and 2020. The sample includes 1144 women in Nigeria and 347 women in Côte d'Ivoire who reported having ever experienced an abortion. We assess partner involvement in discussing the abortion decision and/or in selecting the method or source and evaluate the relationship between partner involvement and most unsafe abortion (using non-recommended methods from a non-clinical source) versus safe or less safe abortion, adjusting for sociodemographic characteristics. Results We find a strong association between experiencing any partner involvement and decreased odds of experiencing a most unsafe abortion (Nigeria: aOR = 0.34, 95% CI 0.26-0.45; Côte d'Ivoire: aOR = 0.27, 95% CI 0.16-0.47). Analyzing the two types of partner involvement separately, we find that partner involvement in the decision is associated with lower odds of most unsafe abortion in both countries (Nigeria: aOR = 0.48, 95% CI 0.39-0.72; Côte d'Ivoire: aOR = 0.34, 95% CI 0.19-0.60); partner involvement in selecting the method and/or source was only significantly associated with lower odds of most unsafe abortion in Nigeria (Nigeria: aOR = 0.53, 95% CI 0.39-0.72; Côte d'Ivoire: aOR = 0.65, 95% CI 0.32-1.32). Conclusion In Nigeria and in Côte d'Ivoire, respondents whose partners were involved in their abortion trajectory experienced safer abortions than those whose partners were not involved. These findings suggest the potential importance of including men in education on safe abortion care and persistent need to make safe abortion accessible to all, regardless of partner support.